Creutzfeldt-Jakob Disease and Infection Control - Lynn Johnston; John Conly (Canadian Journal of Infectious Diseases)
Over the past year, several situations have occurred in Canada in which patients who had recently undergone a surgical procedure were subsequently diagnosed with confirmed or suspected Creutzfeldt-Jakob disease (CJD). This raised concerns over contamination of surgical instruments: which instruments might have been contaminated from direct exposure to tissues; can instruments become cross-contaminated by exposure to other contaminated instruments; what assessment is necessary to determine cross-contamination; and what should be done with instruments that have been contaminated. Additionally, should there be a patient traceback in the face of potential but unproven exposure? Unfortunately, there are no easy answers to most of the above questions. Australia, the United Kingdom and the World Health Organization have developed guidelines for the infection control management of patients with CJD, as well as instruments and devices that come into contact with them and their tissues (1-3). Health Canada's draft CJD infection control guidelines, withdrawn from the Health Canada Web site until safety concerns regarding sodium hydroxide can be addressed, closely mirrored recommendations made in those documents. The Centers for Disease Control and Prevention guidelines for CJD are under revision. However, a recent American publication made recommendations on what procedures should be used for reprocessing items that have been in contact with the prion protein (PrP) (4). These recommendations differ substantially from the draft Canadian guidelines. This article reviews current knowledge about CJD, and highlights some of the infection control concerns and controversies.